Kasani kah muridi khitabi Kumitahi-yi Markazi-yi kha'ini Hizbi Tudah qarar giriftahand, Chirikhai-yi Fada'i-yi Khalq nistand! (Sazmani Chirikha-yi Fada'i-yi Khalqi Iran)
Those who have been addressed by the treacherous Central Committee of the Tudah Party are not the Organization of the Iranian People's Guerrilla Freedom Fighters!